1998
DOI: 10.1152/ajplung.1998.275.1.l165
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of pleural mesothelioma cell lines to apoptosis: relation to expression of Bcl-2 and Bax

Abstract: A failure of normal apoptosis, often due to mutant p53, may contribute to the formation of a cancer and to its resistance to therapy. Mesothelioma, an asbestos-induced tumor, is highly resistant to therapy but generally expresses wild-type p53. We asked whether mesothelioma was resistant to apoptosis and whether resistance was associated with altered expression of the antiapoptotic protein Bcl-2 or proapoptotic protein Bax. We found that three mesothelioma cell lines (1 with wild-type p53) were highly resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
81
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 36 publications
3
81
1
Order By: Relevance
“…We and others have previously demonstrated that MM cell lines show low susceptibility to TRAIL (Liu et al, 2001;Tomasetti et al, 2004) (Vivo et al, 2003) and that this is not due to Bcl-2 (Narasimhan et al, 1998). Here, we show that, although MM primary cells and cell lines express Fas and DR4/DR5, they are not killed by their crosslinking.…”
Section: Introductionsupporting
confidence: 59%
“…We and others have previously demonstrated that MM cell lines show low susceptibility to TRAIL (Liu et al, 2001;Tomasetti et al, 2004) (Vivo et al, 2003) and that this is not due to Bcl-2 (Narasimhan et al, 1998). Here, we show that, although MM primary cells and cell lines express Fas and DR4/DR5, they are not killed by their crosslinking.…”
Section: Introductionsupporting
confidence: 59%
“…Because mesothelioma is a tumor highly resistant to therapy, strategies that would enhance its response to chemotherapy could provide a useful therapeutic adjunct (37). Mesothelioma most likely has abnormal function of the p53 pathway, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In primary fibroblasts with targeted gene disruption of JNK1 and JNK2, JNK-induced apoptosis has been shown to depend on its actions at the mitochondria (36) and to require the presence of the pro-apoptotic members of the Bcl-2 family, Bax and Bak (53). We have previously shown that mesothelial cell lines, including M28 and REN, highly express Bax and postulated that this would allow the cells to respond to appropriate apoptotic signals directed to the mitochondria (37). In that case, perhaps, enhanced JNK signals caused by TRAIL plus etoposide would be sufficient to sensitize the mitochondria to respond to TRAILinduced BID signals, mediating synergy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, resistance to apoptosis could explain MM's striking insensitivity to traditional therapy. Asbestos fibers cause apoptosis of normal mesothelial cells; however, mesothelioma cell lines are resistant to apoptosis due to exposure to asbestos fibers, H 2 O 2 , and calcium ionophore (5). This resistance to apoptosis is not affected by the presence of p53, and Bcl-2 is not overexpressed in mesothelioma cells.…”
Section: Introductionmentioning
confidence: 97%